Isoflavones inhibit poly(I:C)-induced serum, brain, and skin inflammatory mediators - relevance to chronic fatigue syndrome. - Vasiadi, Magdalini.; Newman, Jennifer.; Theoharides, Theoharis C. (2016)
Background: Chronic Fatigue Syndrome (CFS) is a neuroimmunoendocrine disease affecting about 1% of the US population, mostly women. It is characterized by debilitating fatigue for six or more months in the absence of cancer or other systemic diseases. Many CFS patients also have fibromyalgia and skin hypersensitivity that worsen with stress. Corticotropin-releasing hormone (CRH) and neurotensin (NT), secreted under stress, activate mast cells (MC) necessary for allergic reactions to release inflammatory mediators that could contribute to CFS symptoms.; Keywords: Brain, Fatigue, Inflammation, Isoflavones, Mast cells, Polyinosinic:polycytidylic acid, Skin, Stress, Swim.; Springer Open.